Unjuk Kerja Pembangkit Listrik Tenaga Uap: Studi di PT Bumi Sawit Sukses Pratama Bangka Belitung - Sandi, Rizky Wira; Sunanda, Wahri; Puriza, M. Yonggi (ELECTRON Jurnal Ilmiah Teknik Elektro, 2021)
Utilization of solid waste oil palm from PT Bumi Sawit Sukses Pratama in Bangka Belitung Islands Province). As a source of raw material for electrical energy, it is one of the choices among other new energy sources to meet the needs of electrical energy other than PLN. For steam power plants that are run, the system is supported by a turbine with a capacity of 2 MW and 2 boilers with a capacity of 45 tons / hour each which are operated alternately. The lowest unit 1 boiler efficiency was obtained 39% and the highest was 49%. Meanwhile, the lowest efficiency in boiler unit 2 was 39% and the highest was 49%. Then for steam production in boiler unit 1 the highest is 34,300 kg / hour and the lowest is 27,500 kg / hour. Then for the production of steam boiler unit 2, the highest is 34,800 kg / hour and the lowest is 27,500 kg / hour